Political Interference And Democratic Governance In Nigeria: Implications For Local Government (Journal of Namibian Studies : History Politics Culture, 2023)
This paper examined relationship between political interference and democratic governance within the context of local government administration in Nigeria, with a specific focus on Ogun, Osun, and Ekiti states. A descriptive approach was employed to collect comprehensive data, with a sample size of 300 respondents including local government officials, politicians, civil society activists, and scholars in political science. The findings reveal that political interference is a pervasive issue, with approximately 90% of respondents reporting instances of interference. Despite the existence of legal and policy frameworks aimed at safeguarding local government autonomy and preventing interference, respondents indicated that such frameworks are not consistently effective. Consequently, political interference erodes trust and confidence in local government authorities, raising questions about the adequacy of existing mechanisms.